2017
DOI: 10.1111/bph.13907
|View full text |Cite
|
Sign up to set email alerts
|

The Arg–Phe‐amide peptide 26RFa/glutamine RF‐amide peptide and its receptor: IUPHAR Review 24

Abstract: This article, contributed by members of the International Union of Basic and Clinical Pharmacology Committee on Receptor Nomenclature and Drug Classification (NC-IUPHAR) subcommittee for the QRFP receptor, confirms the existing nomenclature for this receptor, and reviews our current understanding of its structure, pharmacology and functions, and likely physiological roles in health and disease. More information on this receptor can be found in the Concise Guide to PHARMACOLOGY The RFamide neuropeptide 26RFa wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 194 publications
(627 reference statements)
0
39
0
Order By: Relevance
“…The peptide QRFP begins with the amino acid glutamine (Q) and ends with RFamide, thereby resembling other RFamide peptides and the RYamide peptides NPY and PYY ( Elphick and Mirabeau, 2014 ; Leprince et al, 2017 ). QRFP was discovered independently in frog and mammalian brain, and a single gene has been found throughout the vertebrates ( Leprince et al, 2017 ). In the hypothalamus, QRFP can potently stimulate food intake ( Leprince et al, 2017 ).…”
Section: Neuropeptides and Their Receptors In Vertebrates – The Impacmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide QRFP begins with the amino acid glutamine (Q) and ends with RFamide, thereby resembling other RFamide peptides and the RYamide peptides NPY and PYY ( Elphick and Mirabeau, 2014 ; Leprince et al, 2017 ). QRFP was discovered independently in frog and mammalian brain, and a single gene has been found throughout the vertebrates ( Leprince et al, 2017 ). In the hypothalamus, QRFP can potently stimulate food intake ( Leprince et al, 2017 ).…”
Section: Neuropeptides and Their Receptors In Vertebrates – The Impacmentioning
confidence: 99%
“…QRFP was discovered independently in frog and mammalian brain, and a single gene has been found throughout the vertebrates ( Leprince et al, 2017 ). In the hypothalamus, QRFP can potently stimulate food intake ( Leprince et al, 2017 ). A single QRFP receptor has been described in mammals ( Fig.…”
Section: Neuropeptides and Their Receptors In Vertebrates – The Impacmentioning
confidence: 99%
“…26RFa (also referred to as pyroglutamyl RFamide peptide (QRFP)) is a hypothalamic neuropeptide discovered concurrently by us and others 10–12. 26RFa has been characterized in all vertebrate phyla including human,13 14 and identified as the cognate ligand of the human orphan G protein-coupled receptor, GPR103 11–13 15 16. Neuroanatomical observations revealed that 26RFa-expressing and GPR103-expressing neurons are primarily localized in hypothalamic nuclei involved in the control of feeding behavior 10 11 15 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…26RFa (also referred to as QRFP) is a hypothalamic neuropeptide discovered concurrently by us and others (10-12). 26RFa has been characterized in all vertebrate phyla including human (13, 14), and identified as the cognate ligand of the human orphan G protein-coupled receptor, GPR103 (11-13,15, 16). Neuroanatomical observations revealed that 26RFa- and GPR103-expressing neurons are primarily localized in hypothalamic nuclei involved in the control of feeding behaviour (10,11,15,17,18).…”
Section: Introductionmentioning
confidence: 99%